Cavernous Branched Nerve Regeneration Using Non-Tubular Artificial Nerve Sheets Using Freeze-Dried Alginate Gel Combined With Polyglycolic Acid Mesh in a Rat Model. Issue 1 (12th January 2021) - Narita, Shintaro; Obara, Takashi; Ishikawa, Namiko; Suzuki, Yoshihisa; Habuchi, Tomonori
Abstract: Introduction: Neuroprotection and neuroregeneration of cavernous nerve plexus by biological/bioengineering solutions may have the potential to maintain erectile function. Aims: We evaluated the efficacy of a newly developed artificial nerve sheet using freeze-dried alginate (ALG) with polyglycolic acid (PGA) mesh in a rat model. Methods: Bilateral cavernous nerves of male rats were excised to make an approximately 2 mm gap. A piece of the sponge-like freeze-dried sheet created by covalent cross-linking of ALG gel combined with PGA mesh was placed over the gap to cover each stump without any neural anastomosis. We compared erectile functions in the ALG groups with those in the sham group and the bilateral nerve excision group (n = 12, each). Main Outcome Measures: Main outcome measure was a rat model with cavernous nerve excision. Results: All rats in the sham group had erection at 63 or 64 days, and mating behavior was confirmed in 10 rats (83.3%) of the sham group at 56 to 62 days. No erection and mating behavior was observed in the excision group. Ten of the 12 (83.3%) rats in the ALG group had a mating behavior and an erection, and the rates of erection and mating behavior were significantly higher in the ALG group than those in the excision group ( P  < .01, P  < .01, respectively). Using a retrograde FluoroGold, the rate of FluoroGold positive pelvic ganglia proximal to the gap at 61 or 62 days was significantly higher in the ALG group than that in the excision group ( P  = .014). Conclusion: The results of our animal study have demonstrated that simply filling the cavernous nerve gap using the non-tubular artificial nerve sheets made of ALG with PGA mesh restored erectile function after cavernous nerve excision.